2013
DOI: 10.1172/jci65767
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular degradation of TRKB by MMP9 in the diabetic brain

Abstract: Diabetes elevates the risk for neurological diseases, but little is known about the underlying mechanisms. Brain-derived neurotrophic factor (BDNF) is secreted by microvascular endothelial cells (ECs) in the brain, functioning as a neuroprotectant through the activation of the neurotrophic tyrosine kinase receptor TRKB. In a rat model of streptozotocin-induced hyperglycemia, we found that endothelial activation of MMP9 altered TRKB-dependent trophic pathways by degrading TRKB in neurons. Treatment of brain mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 15 publications
0
20
1
2
Order By: Relevance
“…In the normal state, retinal endothelial cells secret BDNF to support RGC, whereas the secretion of MMP9 is suppressed. Navaratna et al (50,51) revealed that endothelial cells of diabetic rats express decreased BDNF levels and increased MMP9 protein. Abnormal expression of MMP9 is associated with glaucomatous alterations (52).…”
Section: Discussionmentioning
confidence: 99%
“…In the normal state, retinal endothelial cells secret BDNF to support RGC, whereas the secretion of MMP9 is suppressed. Navaratna et al (50,51) revealed that endothelial cells of diabetic rats express decreased BDNF levels and increased MMP9 protein. Abnormal expression of MMP9 is associated with glaucomatous alterations (52).…”
Section: Discussionmentioning
confidence: 99%
“…In models of diabetes, advanced glycation end-products lead to MMP9 secretion by endothelial cells and cleavage of the ectodomain of the BDNF receptor TRKB on neurons, reducing neurotrophic signaling (Navaratna et al, 2013). Owing to their trophic support of vascular cells, dysfunction and damage to neurons and glia is associated with endothelial cell atrophy and microvascular rarefaction (Brown and Thore, 2011).…”
Section: Pathogenic Mechanisms Responsible For White Matter Injurymentioning
confidence: 99%
“…Antioxidants including vitamin C, free radical scavengers and mimetics of antioxidant enzymes have been shown to attenuate the deleterious effects of high glucose [122]. Exposure of HBMECs to AGEs results in increased MMP9 activation, leading to the degradation of TRKB, a BDNF receptor [123]. Decreased viability of endothelial cells is observed following the silencing of SIRT3, a mitochondrial sirtuin that increases the activities of metabolic enzymes by deacetylation [124].…”
Section: Damage To the Blood Brain Barrier (Bbb)mentioning
confidence: 99%